Effect of thalamic deep brain stimulation on swallowing in patients with essential tremor. Issue 7 (16th June 2020) - Lapa, Sriramya; Claus, Inga; Reitz, Sarah C.; Quick‐Weller, Johanna; Sauer, Sonja; Colbow, Sigrid; Nasari, Christiane; Dziewas, Rainer; Kang, Jun‐Suk; Baudrexel, Simon; Warnecke, Tobias
Abstract: Objective: Deep brain stimulation (DBS) of the ventral intermediate nucleus (VIM) is a mainstay treatment for severe and drug‐refractory essential tremor (ET). Although stimulation‐induced dysarthria has been extensively described, possible impairment of swallowing has not been systematically investigated yet. Methods: Twelve patients with ET and bilateral VIM‐DBS with self‐reported dysphagia after VIM‐DBS were included. Swallowing function was assessed clinically and using by flexible endoscopic evaluation of swallowing in the stim‐ON and in the stim‐OFF condition. Presence, severity, and improvement of dysphagia were recorded. Results: During stim‐ON, the presence of dysphagia could be objectified in all patients, 42% showing mild, 42% moderate, and 16 % severe dysphagia. During stim‐OFF, all patients experienced a statistically significant improvement of swallowing function. Interpretation: VIM‐DBS may have an impact on swallowing physiology in ET‐patients. Further studies to elucidate the prevalence and underlying pathophysiological mechanisms are warranted.